Activated carbon- supported Vanado-nickelate (IV) based hybrid materials for energy application. (August 2021) - Maity, Sukanya; BM, Neethu; Kella, Tatinaidu; Shee, Debaprasad; Das, Partha Pratim; Mal, Sib Sankar
Highlights: The 15 Wt.% of NiV in the AC-NiV14 electrode shows a high specific capacitance value of 316 F/g at 1 A/g current density. The AC-NiV14 electrode offers a remarkable energy density of 63.2 Wh/kg at 1 A/g current density. The potential window increased up to 1.6 V for the asymmetric AC//AC-NiV14 electrode and enhanced the energy and power densities of about 90.1 Whkg −1 and 2400 Wkg −1, respectively, with 98% coulombic efficiency. The AC-NiV14 //NiV14 asymmetric cell possesses 375 Fg −1 with a maximum power of 3140 Wkg −1 at the high current density of 2 Ag −1 . Abstract: The rapid development of supercapacitor (SC) technology leads to increased demand for nanofabrication of novel and effective electroactive hybrid materials for next-generation energy storage devices. Herein, nickel tetradecavanadate, K2 H5 [NiV14 O40 ](NiV14 ), is doped into porous activated carbon (AC), for the first time, in different wt.% in order to investigate the homogeneous loading of the inorganic metal-oxide component on the AC matrix. The resulting complex, AC-NiV14, is found to have possessed an enhanced electrochemical characteristic (for both symmetric and asymmetric SC cell), which operates at a significantly higher potential of 1.2 V. The combination of the double-layer capacitance (EDLC) and the redox-active polyoxometalate cluster leads to an intrinsic increase in specific capacitance (capacity) (from 45.3 Fg −1 (54.4 Cg −1 ) for AC to 316 Fg −1 (379.2 Cg −1 ) for 15 wt.% AC-NiV14 at a current density of 1 Ag −1 ). It was also observed that there is an increase of 20% in the operating voltage compared to conventional AC supercapacitors with acidic aqueous electrolytes. Firstly, symmetric supercapacitor's electrochemical performances of various wt.% of NiV14 composition were studied in acidic aqueous electrolyte (0.5 M H2 SO4 ) solution. We observed that the 15 wt.% of AC-NiV14 hybrid electrode showed remarkable specific energy value ( 63.2 Wh kg −1 ) compared with pristine AC and NiV14 electrodes, separately. Besides, the asymmetric layout (AC//AC-NiV14 ) increased the potential window up to 1.5 V and enhanced the specific energy and power values (90.1 Whkg −1 and 2400 Wkg −1, respectively), with 98% coulombic efficiency. Meanwhile, the AC-NiV14 //NiV14 asymmetric cell possesses a specific capacitance (capacity) of 375 Fg −1 (450 Cg −1 ) with a maximum power of 3140 Wkg −1 at the high current density of 2 Ag −1 .